Plotting Crime: Comparing Representations of the Spatial Distribution of Crime in an Urban Context - Yaraskovitch, Alyson A. (Université d'Ottawa / University of Ottawa, 2013)
Over the past few decades, research into public perceptions of crime has largely focused on how mass media consumption shapes beliefs about crime. Substantially less research has been dedicated to exploring the potential influence of alternative sources of information, and even less attention has been devoted to exploring the spatiotemporal aspect of perceptions of crime. This thesis combined Geographic Information Systems (GIS) and structured interviews in order to explore the narratives about crime constructed by three sources: (1) the Ottawa Police Service, (2) the Ottawa Citizen newspaper, and (3) residents of Ottawa. Eight participants were taken on a walking tour interview, and their responses were compared to two maps depicting the geographies of crime presented by the Ottawa Police Service and the Ottawa Citizen. It was found that the places participants believed to be criminal ones were poorly maintained and dirty, were populated by large numbers of homeless individuals, had little to no commercial space, were geographically close to other areas of the city believed to be criminal spaces, and were poorly lit. The three construction of the spatial distribution of crime in Ottawa shared many common features (such as a focus on the Byward Market area as highly criminal) while remaining distinct in their presentation of certain types of spaces (such as the newspaper’s presentation of homeless shelters as highly criminal spaces). Ultimately, this thesis explores three distinct narratives about the geography of crime in Ottawa through the use of a unique mixed methods design that provides an alternative way of interpreting data most commonly analyzed through deductive or quantitative means.
Keywords: crime; criminology; geography; Ottawa; mixed methods; qualitative; map; GIS